Implementasi Gaya Kepemimpinan Transformasional Kepala Badan Kepegawaian dan Pelatihan Sumber Daya Manusia (BKPSDM) di Bintan, Kepulauan Riau - Ananta, Adelia Septi; Asfar, Hilda; Faris, Salman; Satriadi (Jurnal EMT KITA, 2025)
This study aims to analyze the implementation of transformational leadership style among employees at the Human Resources and Personnel Training Agency (BKPSDM) in Bintan, Riau Islands. This research uses a descriptive qualitative method through interviews and questionnaires involving the Head of the Agency, Mr. Drs. Edi Yusrial. The data were analyzed using thematic analysis and triangulation techniques to ensure validity. The findings highlight the importance of applying transformational leadership in dynamic governmental organizations. The results show that BKPSDM Bintan Regency implements a focused transformational leadership style aimed at employee development. Transformational leaders encourage employees to be innovative, creative, and to grow both personally and professionally through effective communication. The Head of BKPSDM emphasizes the importance of shared goals in decision-making, as well as prioritizing collaboration between leaders and staff. Regular coordination meetings are held to align activities across sub-divisions, evaluate employee performance, and provide training based on identified needs to address division gaps. Planning, organizing, directing, and controlling serve as the main foundations in team operations at BKPSDM. These findings offer insights for management in formulating an effective and innovative leadership style implementation at BKPSDM. This study also provides recommendations to ensure the transformational leadership style is understood more comprehensively. It is expected that the organization can identify its strengths and weaknesses in implementation, and formulate more effective development strategies in the future.
Keywords: Transformational Leadership Style; Motivation; Human Resource Development; Employee Performance